A comparative study on the role of attitude motivation, and language learning strategies towards English as a foreign language among Vietnamese college students in HCM City, Vietnam - Vu, Lan Thi Ngoc (Animo Repository, 2013)
This comparative study on the role of attitudes (positive and negative attitude), motivations (instrumental and integrative motivation), and language learning strategies (LLS which may be direct and indirect strategies) in learning English as a foreign language (FL) involved 193 male and female freshmen and sophomore college students majoring in English, Psychology and Sociology in the University of Social Sciences and Humanities (USSH) in Ho Chi Minh City, Vietnam. The study employed a mixed method research design. The quantitative study consisted of a survey using two different survey questionnaires: The first one, the AMTB developed by Gardner (1985) and associates, was used to measure the attitudes and motivations toward English as a FL of Vietnamese EFL learners the second one is the Strategy Inventory for Language Learning (SILL) developed by Oxford (1990) to measure LLS. The qualitative study employed a semi-structured interview with 45 participants. Descriptive statistics (means and standard Deviations), Independent t-test, and Pearson r Correlation analysis were used to analyse the data and to answer the five research questions raised in the study. Regarding attitudes and motivations towards English learning, the results of the study revealed that Vietnamese EFL college students tended to have significant positive attitudes towards English, and they appeared to be instrumentally and integratively motivated to learn English. Interestingly, the findings showed that there was a significant difference between males and female attitudes towards English as a FL however, there was no significant difference found in motivation and LLS between male and female students. Additionally, at p < .001 alpha level, there was a significant and positive correlation between LLS and attitudes, and LLS and motivation. These findings suggest that attitudes, motivations and LLS play an important role for Vietnamese EFL college learners, particularly for those who are not English majors. Furthermore, he differences between males and females in English language learning also suggest that language teaching strategies should be given more attention by teachers and educators. Last but not least, the findings also the revealed that there were significant correlations between these variables. This suggests that students with more positive attitudes and motivations use better LLS; corollary to this, the clearer is the understanding about LLS, the more appropriate are the LLS used by EFL learners; a more positive attitude also increases the motivation of EFL. The implications of these findings and recommendations based on them are also discussed in the study.